The Role of Islamic Education in Building the Faith Resilience of the Younger Generation in the Era of Globalization - Hidayah, Nurul; Bin Salman, Abdul Matin; Munadi, Muhammad; Al Rasyid, Ahmad Ridwan; Windarto, Cahyani (Suhuf: International Journal of Islamic Studies, 2026)
Background: Globalization poses a significant threat to the religious identity and faith resilience of Indonesian Muslim youth, reflecting a gap between national policies on Islamic education and their practical implementation. Objective: This study aims to explore operational management strategies to effectively implement Islamic educational values and foster genuine faith resilience among the younger generation. Methodology: Employing a qualitative descriptive approach with a narrative review, this research analyzes data from Sinta-accredited journals and national policy documents (2020–2025). Thematic and comparative analyses were conducted across theoretical, practical, and policy dimensions. Results: Findings reveal that Islamic education integrates theoretical foundations such as tazkiyat al-nafs with practical implementation in institutions such as madrasas and pesantrens. However, implementation challenges include regulatory fragmentation, inadequate teacher training, and limited community participation. Conclusion: Islamic education is crucial for nurturing faith resilience but necessitates an integrated management strategy. Policymakers should prioritize a collaborative governance model, grounded in shura and contingency theory, to enhance inter-institutional synergy and develop context-sensitive, actionable policies